2021
DOI: 10.7759/cureus.13701
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Combined Major Arterial and Lumbar Plexus Injury During Primary Extra Lateral Interbody Fusion: Case Report and Review of the Literature

Abstract: Extra lateral interbody fusion (XLIF) has been established in recent years as an effective approach to address degenerative lumbar disc disease (DLDD). Although neurological and vascular complications during XLIF have been reported, to our knowledge, a combination of simultaneous vascular and neurovascular complication during XLIF has not been reported to date. A 72-year-old female patient was admitted to our orthopaedic department because of back pain associated with severe neuropathic radicular pain to her b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Varying frequencies of major vascular injuries/surgical errors have been reported during XLIF (0% up to 1.8%), OLIF (up to 3.2%), and LLIF (up to 2%) [ Table 1 ]. [ 2 , 4 , 5 , 10 , 16 - 18 , 20 ]…”
Section: Varying Frequencies Of Major Vascular Injuries Caused By Xli...mentioning
confidence: 99%
See 3 more Smart Citations
“…Varying frequencies of major vascular injuries/surgical errors have been reported during XLIF (0% up to 1.8%), OLIF (up to 3.2%), and LLIF (up to 2%) [ Table 1 ]. [ 2 , 4 , 5 , 10 , 16 - 18 , 20 ]…”
Section: Varying Frequencies Of Major Vascular Injuries Caused By Xli...mentioning
confidence: 99%
“…In an effort to limit major vascular injuries occurring during XLIF, OLIF, and LLIF procedures, multliple authors recommended obtaining preoperative radiological studies to document the anatomy of the lumbar great vessels [ Table 1 ]. [ 1 , 2 , 4 , 5 , 10 , 16 - 18 , 20 ] Alkadhim et al . (2015) emphasized that; “Understanding the vascular anatomy of the lateral and anterior lumbar spine is paramount for successfully and safely executing the LLIF procedure” [ Table 1 ].…”
Section: Varying Frequencies Of Major Vascular Injuries Caused By Xli...mentioning
confidence: 99%
See 2 more Smart Citations
“…Assina et al reported a fatal case involving extensive lacerations to the inferior vena cava (IVC) and both common iliac veins (CIVs) related to anterior longitudinal ligament (ALL) retractor migration during an L4–L5 LLIF from a right-sided approach ( 22 ). Buric et al described a right CIV injury that occurred during Cobb elevator dissection of the L4–L5 disc from the L4 inferior end plate during a right-sided LLIF approach, while Mousafeiris et al reported an aortic laceration and right common iliac artery (CIA) injury during the cage placement at L4–L5 from a left-sided approach ( 23 , 24 ). Kueper et al reported one case of an abdominal aorta injury during a L3–L5 LLIF ( 25 ).…”
Section: Introductionmentioning
confidence: 99%